THE ROLE OF MEITEI WOMEN IN SOCIO-ECONOMIC DEVELOPMENT IN MANIPUR - Devi, Mangshatabam Kritibala; Devi, SH. Shantibala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Manipur is traditionally a male-dominated society, yet Meitei women have played a pivotal role in shaping the nation's development. They have made significant contributions to both the economic and cultural spheres, showcasing remarkable independence and courage. These qualities remain deeply ingrained in the Meitei women of Manipur, who continue to actively participate in various economic and social activities. Historically, Manipur's economy was agrarian, with the Khwairamband Bazar serving as its economic hub. Beyond their domestic responsibilities, Meitei women have been instrumental in supplementing family income and securing their livelihoods. They can be categorized into three main groups: self-employed workers, wage earners, and unpaid family helpers. Their contributions have been vital to the socio-economic development of the region. Meitei women have also been at the forefront of several significant movements. These movements highlight the crucial role women have played in shaping Manipur's economic and social landscape. To further their socio-economic agenda, the Macha Leima organization was established as a platform for women to evaluate and advance their programs. Through their resilience and activism, Meitei women have left an indelible mark on the state's history and continue to be a driving force in its progress.